Flipped classroom–digital game based learning (FC-DGBL): Enhancing genetics conceptual understanding of students in bilingual programme: Research Article - Ristanto, Rizhal Hendi; Kristiani, Endah; Lisanti, Elsa (Journal of Turkish Science Education, 2022)
The learning process with modern technology is an absolute requirement in the digital age. As a science subject with unique characteristics, biology also requires a unique and technology-based learning process. Flipped Classroom-Digital Game-Based Learning (FC-DGBL) is a learning model that combines flipped classrooms and evaluations using digital game-based learning Kahoot. This study on the effect of the FC-DGBL learning model on the conceptual understanding of Genetics was conducted on secondary school students in the grade nine bilingual program. The research was located at Penabur Christian Secondary School Kelapa Gading Jakarta, Indonesia. This study used a quasi-experimental design; the students involved were 46 students, and data on understanding genetic concepts were collected using a 12-question essay test that refers to Bloom’s taxonomy. The analysis was performed by ANCOVA testing at the significance level a = 0.05. The results showed that FC-DGBL had a significant effect to enhance the conceptual understanding of the Genetics of bilingual secondary school students. Students who obtained the Flipped Classroom-Digital Game-Based Learning (FC-DGBL) significantly understood the Genetics concept than students with traditional learning models. Based on the dimensions of conceptual genetics understanding in the aspect of applying genetic knowledge, analyzing the concept of genetics, and proposing new ideas about genetics FC-DGBL had a higher increase, whereas the evaluating aspect of ideas related to genetics was lower than that of the control group. FC-DGBL is a good learning design for learning genetics in bilingual learning programs.